Loss of H2A.Z Is Not Sufficient to Determine Transcriptional Activity of Snf2-Related CBP Activator Protein or p400 Complexes - Tamara A. Bowman; Madeline M. Wong; Linda K. Cox; Joseph J. Baldassare; John C. Chrivia (International Journal of Cell Biology)
The p400 and SRCAP (Snf2-related CBP activator protein) complexes remodel chromatin by catalyzing deposition of histone H2A.Z into nucleosomes. This remodeling activity has been proposed as a basis for regulation of transcription by these complexes. Transcript levels of p21 or Sp1 mRNAs after knockdown of p400 or SRCAP reveals that each regulates transcription of these promoters differently. In this study, we asked whether deposition of H2A.Z within specific nucleosomes by p400 or SRCAP dictates transcriptional activity. Our data indicates that nucleosome density at specific p21 or Sp1 promoter positions is not altered by the loss of either remodeling complex. However, knockdown of SRCAP or p400 reduces deposition of H2A.Z∼50% into all p21 and Sp1 promoter nucleosomes. Thus, H2A.Z deposition is not targeted to specific nucleosomes. These results indicate that the deposition of H2A.Z by the p400 or SRCAP complexes is not sufficient to determine how each regulates transcription. This conclusion is further supported by studies that demonstrate a SRCAPΔATP mutant unable to deposit H2A.Z has similar transcriptional activity as wild-type SRCAP.